A CRITICAL ASSESSMENT OF THE EFFICACY OF THE NIGERIAN ANTI-MONEY LAUNDERING LEGAL AND INSTITUTIONAL FRAMEWORKS FOR POLITICALLY EXPOSED PERSONS - NWOSU-IHEME, UGOCHUKWU (2021)
THIS THESIS IS FOCUED ON AND PRESENTS THE FIRST SOCIO-LEGAL ANALYSIS AND ASSESSMENT OF THE NIGERIAN ANTI-MONEY LAUNDERING LEGAL AND INSTITUTIONAL FRAMEWORKS, AND THE EFFECTIVENESS OF THESE LAWS IN COMBATING THE PREVALENCE OF MONEY LAUNDERING ACTIVITIES OF POLITICALLY EXPOSED PERSONS IN NIGERIA. THE STUDY, INTER ALIA, CRITICALLY EXPLORES THE POLITICAL, CONSTITUTIONAL AND LEGAL CHALLENGES THAT IMPEDES THE IMPLEMENTATION OF ANTI-CORRUPTION/ANTI-MONEY LAUNDERING LAWS ON POLITICALLY EXPOSED PERSONS IN NIGERIA. ULTIMATELY, THE RESEARCH PROPOSES A NEW LEGAL MODEL AND TAKES THE POSITION THAT WHAT IS NEEDED IS THE INTRODUCTION OF THE UNEXPLAINED WEALTH ORDERS WHICH PRESENTS LAW ENFORCEMENT WITH MORE OPPORTUNITIES AND GREATER LATITUDE TO FACILITATE THE RECOVERY OF THE PROCEEDS OF CORRUPTION